Pemikir-Pemikir Marxis Dalam Hubungan Internasional - Zahidi, M. Syaprin (Jurnal Ilmiah HUBUNGAN INTERNASIONAL, 2014)
Abstract: Marxism is one of the perspectives in International Relations thats usually we use toexplain the economic international phenomena in the world. At this time, this paper aims to explainthe early development of marxism in international relations. This paper is begin which the explanationabout the opinion from two founding fathers from Marxism they are Karl Marx and Vladimir I. Lenninor usually we call Marxism- classic thinkers. At the last part this paper also continuing with the opinionfrom three key thinkers on Marxism which basic thinking from Marx and Lennin and they are PaulBaran, Andre Gunder Frank and Immanuel Wallerstein, also we call neo-marxian thinkers inInternational Relations.Key Words: International Relations, Marxism, Marxism-classic Thinkers, Neo-marxian Thinkers